Cutting-Edge Topics in Dry Eye Disease - Yoon, Kyung Chul (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This text presents cutting-edge topics on and the diagnostic and therapeutic approaches for tear film abnormities, including dry eye disease and Meibomian gland dysfunction. A new management algorithm for Meibomian gland dysfunction, therapeutic eye drops and intense pulsed lasers for dry eye disease, and topical and systemic agents for neuropathic ocular pain are proposed in this issue.